Performance Analysis Of Parabolic Trough Solar Steam Generators: Acase Of Wenji Pulp And Paper Factory - Abdi Abrahim (ASTU, 2019)
Wenji Pulp And Paper Factory Is One Of The Most Energy Consuming Factory In Which Thermal Energy Is Utilize. In This Factory Thermal Energy Is Used For Drying The Paper .The Main Source Of Thermal Energy For Drying Paper Is Electricity. The Factory Uses Steam Which Has A Temperature Of 215??C For Drying The Paper. This Steam Is Produced Using Resistor Electric Boiler. In Wenji Pulp And Paper Factory, There Are Two Resistor Electric Boilers That Have Different Capacity Of Steam Production. The First One Has A Capacity To Generate 4,302 Kg/Hr Of Steam And The Second One Has Able To Produce 8,600 Kg/Hr Steam At Full Load. This Electric Boiler Is Consuming More Electric Energy And Can Be Partially Or Wholly Replaced By A Solar Parabolic Trough Steam Generator. This Thesis Aims In Performance Analysis Of Parabolic Trough Steam Generation For Wenji Pulp And Paper Factory Which Is Located In Wenji Town. The Simulation Result From Thermal Performance Analysis Study Shows That The Parabolic Trough Steam Generator Can Meet The Steam Demand Of The Factory During The Day. The Parabolic Trough Aperture Area Required To Fulfil This Steam Demand By The Factory Is Obtained To Be Equal To 8,843 M2.During Cloudy Day The Conventional Electric Steam Generation System Can Be Used To Meet The Daily Energy Demand For Generating Steam Only For Few Days In A Year.In This Paper The Required Data Is Collected From Wenji Pulp And Paper Factory And Weather Data Was Taken From Adama Meteorology Agency. Thermal Modelling Of The Parabolic Trough Solar Steam Generator System Is Developed. The Proposed System Functionality Is Tested Using Matlab Software. In Present Study Three Different Mass Flow Rates (0.3kg/S, 0.4kg/S And 0.5kg/S) Are Taken To Test Temperature Of Htf Outlet From Solar Collector. It??S Observed That The Temperature Of Htf Is Inversely Proportional To Mass Flow Rate. So It??S Possible To Increasing Or Decreasing The Temperature Of Htf By Decreasing Or Increasing Mass Flow Rate Respectively. When Mass Flow Rate Of 0.3kg/S Is Flow Through The Collectors; The Outlet Temperature Htf Is Ranged Between 250oc To 340oc.When Mass Flow Rate Of 0.4 Kg/S Is Flow Through The Collectors; The Htf Outlet Temperature Is Ranged Between 220oc To 300oc.When Mass Flow Rate Of 0.5 Kg/S Is Flow Through The Collectors; The Htf Outlet Temperature Is Ranged Between 200oc To 275oc. It??S Observed That With Increasing Mass Flow Rate Htf Temperature Is Decreased. The Corresponding Efficiency Of The System Was Found To Be Equal To 69%. The Optical Efficiency Of Collector Was Higher I.E 75 %.The Maximum Value Of Thermal Efficiency Can Reach Up 68 %.
Acase of Wenji Pulp and Paper Factory